2023
DOI: 10.1002/hep.32612
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐derived MLKL in alcohol‐associated liver disease: Regulation of phagocytosis

Abstract: Background and Aims: Mixed lineage kinase domain-like pseudokinase (MLKL), a key terminal effector of necroptosis, also plays a role in intracellular vesicle trafficking that is critical for regulating liver inflammation and injury in alcohol-associated liver disease (ALD). Although receptor interacting protein kinase 3 (Rip3) −/− mice are completely protected from ethanol-induced liver injury, Mlkl −/− mice are only partially protected. Therefore, we hypothesized that cell-specific functions of MLKL may contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Moreover, the specific functions of MLKL in different cell types could also influence liver inflammation and pathology. A recent study highlighted that the absence of Mlkl specifically in myeloid cells exacerbated ethanol-induced hepatic injury, steatosis, and inflammation in mice (49). Therefore, further research is needed to explore the impact of cell type-specific effects of MLKL on MASH, underscoring the intricate nature of MLKL’s involvement in liver pathology and expanding its potential functions beyond conventional associations with necroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the specific functions of MLKL in different cell types could also influence liver inflammation and pathology. A recent study highlighted that the absence of Mlkl specifically in myeloid cells exacerbated ethanol-induced hepatic injury, steatosis, and inflammation in mice (49). Therefore, further research is needed to explore the impact of cell type-specific effects of MLKL on MASH, underscoring the intricate nature of MLKL’s involvement in liver pathology and expanding its potential functions beyond conventional associations with necroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences have suggested the role of MLKL in regulating immune cells including macrophages. Increased MLKL expression in macrophages was found in ethanol-exposed livers, and myeloid MLKL deficiency exacerbated ethanol-induced steatosis and hepatocyte injury by impairing macrophage phagocytic capability [18]. Inhibition of RIPK1 improves NASH in an MLKL-dependent manner to increase mitochondrial respiration [47].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also showed that alcoholic steatosis-promoted IR injury is independent of MLKL-mediated necroptosis [17]. Moreover, MLKL has been reported to regulate macrophage phagocytosis [18] and hepatocyte autophagy [19] in a necroptosis-independent manner. Therefore, the precise role and underlying mechanism of MLKL in regulating liver IR injury needs to be further studied.…”
Section: Introductionmentioning
confidence: 91%
“…It has been reported that LPS can regulate MLKL expression. Wu et al 21 found that challenging macrophages with LPS-induced phosphorylation of MLKL, as well as translocation and oligomerization of MLKL to intracellular compartments including phagosomes and lysosomes, but not plasma membrane. Knockdown MLKL suppressed the phagocytic capability of primary mouse Kupffer cells at baseline and in response to LPS.…”
Section: Discussionmentioning
confidence: 99%